COMPARATIVE STUDY OF PHALERONYMIC TERMS IN UZBEKISTAN AND ENGLISH (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article investigates the linguistic and cultural features of phaleronymic terms in Uzbekistan and English-speaking countries. Phaleronymy, the branch of terminology that studies the names of orders, medals, and decorations, reflects historical memory, social values, and cultural identity. By analyzing Uzbek and English phaleronymic terms, the study reveals similarities and differences in naming patterns, semantic components, and socio-cultural significance.